Sed lex - Atienza, Venice De Castro (2012)
"Sed lex revolves around the lives of Richard and Nancy. Richard is in his final allowable semester in law school and is facing a financial crisis a month before the semester ends. Nancy is Richard's mother who single handedly raised her son. The financial turmoil takes a toll on Richard and leads him to demand the truth about his father from his mother. Their predicament forces Nancy to come face to face with monsters from her past in order to give Richard the answers to his questions. In the end Richard realizes that he plays a central role in the truth he has long been searching for. The film is about the influence of a higher power - the law and consequences of past decisions in the decision making process of ordinary people. More than anything, it is about making choices amidst difficulty and desperation and the constant struggle to find the truth about the past so that one can have the courage to face the present in order to fight for the future."